(untitled) (Journal of human and social sciences, 2019)
The mere availability of the ability to work is not sufficient; individuals give their best not only in terms of personal or overall productivity, but also in the proper use of raw materials, production tools, adherence to work systems, and collaboration with others. In addition to this ability, there must be a willingness, enthusiasm, and commitment to all matters related to the development of the industrial institution in which individuals work. Given the importance of this topic and its direct relevance to the research subject, the study addresses it in detail through several sections. The first section deals with the definition of motives and their classifications. The second section focuses on incentives, providing their definitions and types. The third section examines the relationship between needs, motives, and incentives. The fourth and final section briefly reviews theories of motivation.